Reduced regional cerebral oxygen saturation increases risk for emergence delirium in pediatric patients - Li, Lijing; Gao, Zhengzheng; Zhang, Jianmin; Zhang, Fuzhou; Wang, Fang; Wang, Xiaoxue; Li, Gan (Frontiers in Pediatrics, 2023)
Objectives: To assess whether decreased regional cerebral oxygen saturation (rScO2) is associated with the emergence delirium (ED) following general anesthesia in the pediatric population Methods: A retrospective observational cohort study was conducted on 113 children (ASA Ⅰ–Ⅲ) aged 2–14 years who underwent selective surgery under general anesthesia between 2022-01 and 2022-04. Intraoperatively, the rScO2 was monitored using a cerebral oximeter. The Pediatric Anesthesia Emergence Delirium (PAED) score was used to evaluate the patients for ED. Results: The incidence of ED was 31%. Low rScO2 was reported in 41.6% of patients, who had a higher incidence of ED (P<0.001) than those who did not experience desaturation. Logistic regression analysis revealed that decreased rScO2 was significantly associated with incident ED events (odds ratio [OR], 10.77; 95% confidence interval, 3.31–35.05). Children under 3 years of age had a higher incidence of ED after rScO2 desaturation during anesthesia compared to older children (OR, 14.17 vs. 4.64). Conclusion: Intraoperative rScO2 desaturation significantly increased the incidence of ED following general anesthesia. Monitoring should be enhanced to improve the oxygen balance in vital organs to improve the quality and safety of anesthesia.